Association between prebiotic, probiotic consumption and hyperuricemia in U.S. adults: a cross-sectional study from NHANES 2011–2018 - Wang, Yixuan; Li, Shiwei; Li, Xin; Wang, Meng; Huang, Bo; Feng, Kailei; Cui, Jingqiu (Frontiers in Nutrition, 2025)
AimThis study aims to provide evidence for an association between the consumption of prebiotics and probiotics and hyperuricemia in U.S. adults.MethodsA total of 7,176 adults who participated in the National Health and Nutrition Examination Survey (NHANES) during 2011–2018 were included in the study. First, the baseline characteristics of the data were described for the weighted data, using the presence or absence of hyperuricemia as the classification criterion. Second, binary logistic regression analyses were performed to establish crude models and regression models adjusted for relevant covariates, and odds ratios (OR) and 95% confidence intervals (95% CI) were calculated to explore the relationship between prebiotics, probiotic intake, and hyperuricemia. Subsequently, receiver operating characteristic (ROC) curves were plotted to assess probiotic consumption’s role in the hyperuricemia prediction model. Finally, subgroup analyses were performed.ResultsParticipants who consumed probiotics had a lower prevalence of hyperuricemia than those who did not (3.48% vs. 6.25%, p = 0.082). In logistic regression analyses, prebiotics’ effect on hyperuricemia was insignificant (p > 0.05), regardless of whether covariates were considered. In contrast, the crude model for probiotics and the adjusted model 1, which was constructed by adjusting for age, sex, and ethnicity, showed ORs less than 1 (crude model: OR = 0.54, 95% CI [0.34, 0.83], p = 0.008; adjusted model 1: OR = 0.54, 95% CI [0.34, 0.83], p = 0.008). The predictive model, including age, sex, race, body mass index (BMI), hypertension, chronic kidney disease, and probiotics, had 76.7% sensitivity and 68.0% specificity with an area under the ROC curve of 0.7886 for detecting hyperuricemia in US adults.ConclusionThese results suggest that probiotic consumption may reduce the incidence of hyperuricemia in the US adult population, but prebiotics have not shown the same effect.